2018
DOI: 10.1257/pandp.20181106
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Incidence and Severity of Food Insecurity by Racial, Ethnic, and Immigrant Groups over the Great Recession in the United States

Abstract: We document the differences in food insecurity incidence and severity by race/ethnicity and immigrant status over the Great Recession. We show that the disadvantaged groups with a higher incidence of food insecurity do not necessarily have a higher severity of food insecurity, which underscores the importance of examining both the extensive and intensive margins of food insecurity. Our decomposition analysis indicates that the contribution of compositional and structural factors to the observed differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The SFIG measure is 33 times greater for the most food insecure group (households headed by a non-White woman with no more than a high school education) as compared to that of the most food secure group (households headed by White men with a college education). Despite strong and positive correlation between prevalence and severity, higher prevalence does not necessarily imply higher severity, consistent with earlier findings based on HFSM data from the CPS (Flores-Lagunes et al 2018). For example, among the female-headed households, those with a non-White head with high school education are more likely to be food insecure than those headed by a White woman without a high school degree, but its SFIG is lower.…”
Section: Groupwise Decompositionsupporting
confidence: 86%
“…The SFIG measure is 33 times greater for the most food insecure group (households headed by a non-White woman with no more than a high school education) as compared to that of the most food secure group (households headed by White men with a college education). Despite strong and positive correlation between prevalence and severity, higher prevalence does not necessarily imply higher severity, consistent with earlier findings based on HFSM data from the CPS (Flores-Lagunes et al 2018). For example, among the female-headed households, those with a non-White head with high school education are more likely to be food insecure than those headed by a White woman without a high school degree, but its SFIG is lower.…”
Section: Groupwise Decompositionsupporting
confidence: 86%
“…Racial disparities in food insecurity have been documented for many years and throughout different economic crises [14,31]. Structural racism contributes to and reinforces the disparately negative effects of food insecurity, which have been exacerbated by COVID-19 [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity prevalence is estimated to be three times higher among non-Hispanic Black households and two times higher among Hispanic households compared to non-Hispanic White households [3]. This discrepancy may be due in part to barriers that prevent equal access to food assistance programs [12][13][14]. For example, a study among Latin American immigrants in Toronto found that barriers to food access were, in part, due to language barriers leading to limited awareness of community food resources and limited availability of culturally preferred foods [15].…”
Section: Introductionmentioning
confidence: 99%
“…Why do these disparities exist? Alfonso Flores‐Lagunes, Hugo Jales, Judith Liu, and I explored differences in food insecurity by race, ethnicity, and immigrant status (Flores‐Lagunes et al, 2018). With the Oaxaca‐Blinder decomposition approach, we controlled for observables that contribute to food insecurity, such as household head's race, age, marital status, and presence of children, among others, and we used instruments to account for the effects of the Supplemental Nutrition Assistance Program (SNAP).…”
Section: Food Security Todaymentioning
confidence: 99%